A 256‐year‐long precipitation reconstruction for northern Kyrgyzstan based on tree‐ring width. (11th September 2019) - Zhang, Tongwen; Lu, Bo; Zhang, Ruibo; Diushen, Mamatkanov; Rysbek, Satylkanov; Bakytbek, Ermenbaev; Chen, Feng; Yu, Shulong; Jiang, Shengxia; Zhang, Heli
Abstract: In this study, 85 tree cores from 45 Schrenk spruces ( Picea schrenkiana ) were used to establish a regional tree‐ring chronology. A 256‐year pJune–May precipitation (where p denotes a month from the previous year) for northern Kyrgyzstan in central Asia was reconstructed using this newly developed chronology. The tree‐ring‐based precipitation reconstruction tracks the observed data well ( r = .622, p < .0001, n = 105). Spatial correlation proved that the reconstructed precipitation series contains climatic signals representative of a larger area, including eastern Kyrgyzstan and parts of Kazakhstan. A comparison between the newly reconstructed precipitation series and four tree‐ring‐based precipitation reconstructions for the surrounding areas reveals similar variations, particularly in the high‐frequency domain. Furthermore, this reconstructed precipitation series matches nine flood (1785, 1786, 1792, 1952, 1953, 1970, 1971, 1973, and 2000) and four drought (1917, 1919, 1927, and 1944) events noted in the historical documents and captures a dry decade that occurred in the 1910s in central Asia. Abstract : A total of 85 tree cores from 45 Schrenk spruces were used to establish a 256‐year June–May precipitation for northern Kyrgyzstan. The precipitation reconstruction not only matches some flood and drought events noted in the historical documents but also captures a dry decade occurred in 1910s in central Asia. During the dry years, the water vapour transport from North Atlantic displaces a northwards shift, resulting in the large‐scale drought from Mediterranean Sea to central Asia.